2020
DOI: 10.21203/rs.3.rs-31660/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nature of dispensing errors in selected hospitals providing free healthcare: A multi-center study in Sri Lanka

Abstract: Background Dispensing errors may result in patient harm. Dispensing errors are preventable if we knew its nature, but only very little information is available on these errors that occur in limited resourced settings where healthcare is provided free of charge. Therefore, the purpose of this study was to determine the types and prevalence of dispensing errors in selected hospitals in Sri Lanka. Methods A prospective, cross sectional and multi-centered study (in one tertiary care and two secondary care hospit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies on dispensing errors have become hot topics in the eld of pharmacy services eld [2][3][4][5][6]. A systematic review and meta-analysis of community pharmacy error rates in the USA showed that dispensing error rates ranged from 0.00003%(43/1420091) to 55%(55/100) [7] between 1993 and 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on dispensing errors have become hot topics in the eld of pharmacy services eld [2][3][4][5][6]. A systematic review and meta-analysis of community pharmacy error rates in the USA showed that dispensing error rates ranged from 0.00003%(43/1420091) to 55%(55/100) [7] between 1993 and 2015.…”
Section: Introductionmentioning
confidence: 99%